2015
DOI: 10.1111/ejn.12851
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A2b receptors control A1 receptor‐mediated inhibition of synaptic transmission in the mouse hippocampus

Abstract: Adenosine is a neuromodulator mostly acting through A1 (inhibitory) and A2A (excitatory) receptors in the brain. A2B receptors (A(2B)R) are G(s/q)--protein-coupled receptors with low expression in the brain. As A(2B)R function is largely unknown, we have now explored their role in the mouse hippocampus. We performed electrophysiological extracellular recordings in mouse hippocampal slices, and immunological analysis of nerve terminals and glutamate release in hippocampal slices and synaptosomes. Additionally, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 82 publications
4
31
0
1
Order By: Relevance
“…In fact, harmaline has been reported to activate 5′‐nucleotidase (an intracellular enzyme which hydrolyzes 5′‐AMP to adenosine), suggesting an increase in adenosine level and release. Adenosine A 1 receptors form heteromers with A 2A or A 2B receptors and with other purinergic receptors, for example, P2Y1 and others, which alters responses mediated by constituent receptors, their sensitivity to endogenous adenosine, ligand binding, and may induce their cross‐antagonism . As some of adenosine heteromers, for example, A 1 with A 2A , and A 2B receptors are localized on glutamatergic terminals, their activation by enhanced endogenous adenosine may mask the antagonistic effect of DPCPX on adenosine A 1 receptor in some brain regions where zif‐268 was analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, harmaline has been reported to activate 5′‐nucleotidase (an intracellular enzyme which hydrolyzes 5′‐AMP to adenosine), suggesting an increase in adenosine level and release. Adenosine A 1 receptors form heteromers with A 2A or A 2B receptors and with other purinergic receptors, for example, P2Y1 and others, which alters responses mediated by constituent receptors, their sensitivity to endogenous adenosine, ligand binding, and may induce their cross‐antagonism . As some of adenosine heteromers, for example, A 1 with A 2A , and A 2B receptors are localized on glutamatergic terminals, their activation by enhanced endogenous adenosine may mask the antagonistic effect of DPCPX on adenosine A 1 receptor in some brain regions where zif‐268 was analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…This is because glutamatergic neurotransmission is a costly process, being responsible for the majority of energetic glucose metabolism in the brain [3]. In concert with this, we recently found that A 2B Rs modulate glutamatergic synaptic transmission in the hippocampus [19]. Not only neurons but also astrocytes are equipped with A 2B R [39,44], and both cell types are capable of releasing glutamate [45].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, A 2B R have been implicated in peripheral glucose homeostasis [15,16] and have been proposed to control astrocytic glycogen metabolism [17,18]. Furthermore, we recently observed that A 2B Rs control A 1 receptor (A 1 R)-mediated responses in hippocampal glutamatergic synapses [19]. These observations prompt the attractive hypothesis that A 2B R may be associated with cerebral glucoregulation, especially when a metabolic boost is needed.…”
Section: Introductionmentioning
confidence: 89%
“…Interestingly, studies have also shown that the A 1 Rs and A 2A Rs form heterodimers that are involved in modulation neurotransmission with stimulation of the A 2A Rs leading to a decrease in agonist affinity for the A 1 Rs [113]. Although the A 2B Rs are expressed at low levels in comparison to the A 2A R in the hippocampus, this receptor has also been shown to regulate A 1 R-mediated inhibition of synaptic transmission [114].…”
Section: Adenosine Receptors (Ars)mentioning
confidence: 99%